Seismic resilient lateral load resisting system for timber structures. (15th September 2017) - Hashemi, Ashkan; Zarnani, Pouyan; Masoudnia, Reza; Quenneville, Pierre
Abstract: Conventional light timber frame buildings made with metal fasteners such as nails, screws, rivets or bolts usually use traditional plywood sheathed shear walls as the main lateral load resisting members. During an earthquake, these structures are prone to large inelastic deformations in the fasteners which lead to drastic stiffness degradation for the system. A damage avoidant seismic solution is being developed to provide the required lateral drift capacity while mitigating the damage through controlled rocking motion. This system includes lateral load resisting members consist of rocking timber panels made of Laminated Veneer Lumber (LVL) and innovative Resilient Slip Friction (RSF) joints as the hold-down connectors at the base. Moreover, a novel type of shear key is introduced to transfer the lateral forces to the foundation. A prototype building is designed and numerically modelled. To investigate the seismic performance, non-linear dynamic time-history simulations were carried out on the system and on similar systems with existing seismic solutions. The results confirm a promising seismic performance in terms of ductility, energy dissipation and self-centring behaviour.